Noise properties of coherent perfect absorbers and critically coupled resonators - Chong, Yidong (2013)
The performance of a coherent perfect absorber (time-reversed laser) is limited by quantum and thermal noise. At zero temperature, the quantum shot noise dominates the signal for frequencies close to the resonance frequency and both vanish exactly at the resonance frequency.We compute the sensitivity of the absorbing cavity as a background-free detector, limited by finite signal or detector bandwidth.